2006
DOI: 10.1080/13880200600596302
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activities of the Methanol Extract ofCardiospermum halicacabum.

Abstract: Cardiospermum halicacabum Linn. (Sapindaceae) is a climber, commonly found as a weed throughout India, used as vegetable as well as traditional medicine for rheumatism, lumbago, and nervous diseases and as demulcent in orchitis and in dropsy. In the current study, we investigated the antioxidant potency of methanol extract of C. halicacabum (CHE) employing various established in vitro systems, such as the b-carotene-linoleate model system, 1,1-diphenyl-2-picrylhydrazyl (DPPH)=superoxide= nitric oxide radical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 28 publications
1
30
0
1
Order By: Relevance
“…The anti-inflammatory activity of ethanol extract of CH reported to inhibit LPS induced COX-2, TNF-α and iNOS expression in RAW264.7 cells (Sheeba, Asha, 2009). Experimental pharmacological studies have shown the analgesic and vasodepressant activities (Gopalakrishnan, Dhananjayan, Kameswaran, 1976), anti-pyretic activity against yeastinduced pyrexia in rats (Asha, Pushpangadan, 1999), anti-malarial (Waako et al, 2005), anti-oxidant activity (Kumaran, Karunakaran, 2006), anti-ulcer activity against ethanol induced gastric ulcer in rats (Sheeba, Asha, 2006) and suppression of the production of TNF-α and nitric oxide in human peripheral blood mononuclear cells (Babu, Krishnakumari, 2006). A number of compounds have been isolated and identified in CH, viz.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-inflammatory activity of ethanol extract of CH reported to inhibit LPS induced COX-2, TNF-α and iNOS expression in RAW264.7 cells (Sheeba, Asha, 2009). Experimental pharmacological studies have shown the analgesic and vasodepressant activities (Gopalakrishnan, Dhananjayan, Kameswaran, 1976), anti-pyretic activity against yeastinduced pyrexia in rats (Asha, Pushpangadan, 1999), anti-malarial (Waako et al, 2005), anti-oxidant activity (Kumaran, Karunakaran, 2006), anti-ulcer activity against ethanol induced gastric ulcer in rats (Sheeba, Asha, 2006) and suppression of the production of TNF-α and nitric oxide in human peripheral blood mononuclear cells (Babu, Krishnakumari, 2006). A number of compounds have been isolated and identified in CH, viz.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-inflammatory properties of CH have been researched [11], but no clinical trials have been reported so far. Experimental pharmacological studies of CH have shown antioxidant activity [12] analgesic and vasodepressant activities [13], antipyretic activity [14], Antimalarial activity [15], diuretic activity [16], anti-diarrheal activity [17], anti-diabetic activity [18] and anti-ulcer activity [19].…”
Section: Introductionmentioning
confidence: 99%
“…This herb act as a diaphoretic, diuretic, emetic, laxative, refrigerant, stomachic and sudorific and has antibacterial (Dhar et al, 1968;Raman et al, 1998), anti-diarrheal (Rao et al, 2006), antioxidant activities (Kumaran and Karunakaran, 2006), suppresses TNF production (Babu and Krishnakumari, 2006), exhibits anticancer (Sheeba and Asha, 2006), vaso depressant (Gopalakrishnan et al, 1976) effect. This herb is also useful in curing of rheumatism, severe bronchitis and firmness of the appendages and snakebite (Abdulla, 1973;Gopalakrishnan et al, 1976;Nadkarni, 1976;Chopra et al, 1980;Joshi et al, 1992).…”
Section: Medicinal Propertiesmentioning
confidence: 99%